Enhancing Environmental Practices and Empowering Communities: A Thematic Community Service Program in Air Kering 1 Padang Guci Kaur Bengkulu - Laura, Fadila Putri; Apriana, Yesi; Putra, Adisi; Sumadi, Delvi; Nurzam, Nurzam; Irwanto, Tito; Suwarni, Suwarni (Universitas Dehasen Bengkulu, 2025)
This account tells the story of the OPTIMISTIS community service day in Desa Air Kering 1, Padang Guci, Kaur, Bengkulu. Over the weekend, volunteers tidied up littered streets, showed children the worth of nature, invited more neighbors to join the clean-ups, and opened spaces where youth could learn. They planted new garbage bins, cleared rubbish from the river, held short Quran classes, and set in the ground forty grafted avocado trees as symbols of pride and extra green in the village. To feel the difference of these tasks, the team watched each day, asked residents through polls and talk circles, then wrote down every answer. Feedback was mostly hopeful: bins stayed full, about eight out of ten adults pitched in, families washed hands more often, and people from different groups chatted more freely. The report now urges village leaders to keep naming caretakers, check the steps together, and guard these small wins before they slowly fade.